"Just Say It Like It Is!" Use of a Community-Based Participatory Approach to Develop a Technology-Driven Food Literacy Program for Adolescents. (January 2018) - Wickham, Catherine A.; Carbone, Elena T.
FuelUp&Go! is a technology-driven food literacy program consisting of six in-person skill building sessions as well as fitness trackers, text messages, and a companion website. A community-based participatory research approach was used with adolescents who were recruited to participate in a Kid Council. Qualitative data were collected about the use of surveys, program activities, recipes, technology and text messages, and music and incentives. Changes suggested by Kid Councilmembers informed the design and development of a pilot program. Participants were recruited for the pilot program and completed pre- and postintervention surveys. The results indicated food-related knowledge remained low but increased from baseline to follow-up. Attitudes toward vegetables and physical activity increased slightly. Self-reported participation in physical activity and consumption of sugar-added beverages moved in positive directions. These findings suggest that community-based participatory research approach is an effective approach to engage adolescents in the development of a technology-driven food literacy program.